Boundless energy: the complete mind-body programme for overcoming chronic fatigue - Chopra, Deepak (Rider London, 1995)
In this text Dr Chopra combines his knowledge of Indian Ayurvedic medicine with Western scientific research to show the significance of the mind/body link and the importance of specific, practical strategies to become better equiped to live a life full of energy, vitality and enjoyment.